The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3987/rev-13-773
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Syntheses of Decalin Type Natural Products

Abstract: This review summarizes the practical synthesis of both enantiomers of chiral intermediate for the syntheses of the natural products possessing the bicyclo[4.4.0]ring system with 4,4,10-trimethyl groups and their application to the total syntheses of the related natural products. Chiral induction was carried out based on enzymatic resolution or optical resolution using chiral auxiliary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…There are four comprehensive reviews on the syntheses of trans-or cis-decalins mainly in isoprenoids (mevalonate)-derived natural products. 3,[12][13][14] However, to the best of our knowledge, reviews compiling different facets of the polyketide decalin have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…There are four comprehensive reviews on the syntheses of trans-or cis-decalins mainly in isoprenoids (mevalonate)-derived natural products. 3,[12][13][14] However, to the best of our knowledge, reviews compiling different facets of the polyketide decalin have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…While there is no recent exclusive review on the synthesis of natural decalins, earlier reports on specic methods or synthetic approaches toward a particular family of compounds may overlap with this review. [1][2][3][4][5][6] In general, decalin synthesis can be classied into two disconnection types (types I and II), according to the order of construction of the two fused cycles A and B. Type I starts with the elaboration of a cyclohexane derivative (corresponding to the cycle A or B) and subsequent C-C bond formations lead to the desired bicyclic system [AB].…”
mentioning
confidence: 99%
“…7 Many of these trans -decalin scaffolds are found in numerous natural products, such as terpenoids and diterpenoids. 8 These decalin systems are privileged structures found in many biologically active natural products and pharmaceutically important compounds. 9…”
mentioning
confidence: 99%